Distinct interaction effects of warming and anthropogenic input on diatoms and dinoflagellates in an urbanized estuarine ecosystem. (28th May 2021) - Cheung, Yan Yin; Cheung, Shunyan; Mak, Julian; Liu, Kailin; Xia, Xiaomin; Zhang, Xiaodong; Yung, Yingkit; Liu, Hongbin
Abstract: Diatoms and dinoflagellates are two major bloom‐forming phytoplankton groups in coastal ecosystems and their dominances will notably affect the marine ecosystems. By analyzing an 18‐year monthly monitoring dataset (2000–2017) in the Pearl River Estuary (one of the most highly urbanized and populated estuarine in the world), we observe an increasing trend of the diatom to dinoflagellate ratio (Diatom/Dino). As revealed by multiple statistical models (generalized additive mixed model, random forest, and gradient boosting algorithms), both groups are positively correlated with temperature. Diatoms are positively correlated with nitrate and negatively correlated with ammonium while dinoflagellates show an opposite pattern. The Diatom/Dino trend is explained by an altered nutrient composition caused by a decadal increase in anthropogenic input, at which nitrate increased rapidly while ammonium and phosphate were relatively constant. Regarding the interaction of warming and nutrient dynamics, we observe an additive effect of warming and nitrate enrichment that promotes the increase in diatom cell density, while the dinoflagellate cell density only increases with warming when nutrients are depleted. Our models predict that the Diatom/Dino ratio will further increase with increasing anthropogenic input and global warming in subtropical estuarine ecosystems with nitrate as the dominant inorganic nitrogen; its ecological consequences are worthy of further investigation. Abstract : We address the interactive effect of warming and anthropogenic nutrient input on two major bloom‐forming phytoplankton groups (diatoms and dinoflagellates) in a highly urbanized estuarine ecosystem by analyzing a decadal long monitoring dataset collected in the Pearl River Estuary (PRE) with multiple statistical models. We find that prolonged nitrate‐dominated anthropogenic input had altered nutrient composition in PRE and leaded to an decadal increase of diatom/dinoflagellate ratio. Our models predict that the Diatom/Dino ratio will further increase with increasing anthropogenic input and global warming in subtropical estuarine ecosystems with nitrate as the dominant inorganic nitrogen; its ecological consequences are worthy of further investigation.